2014
DOI: 10.1111/jora.12174
|View full text |Cite
|
Sign up to set email alerts
|

Do Siblings Matter Independent of Both Parents and Friends? Sympathy as a Mediator Between Sibling Relationship Quality and Adolescent Outcomes

Abstract: The study explored whether sibling affection and hostility were longitudinally associated with adolescents' prosocial, externalizing, and depressive behaviors, after controlling for parent-child and best friend relationship quality. Sympathy was examined as a possible mediator. Three hundred and eight randomly selected families completed Waves 3, 4, and 5 of the Flourishing Families Project. Multiple group comparison via structural equation modeling compared differences between girls and boys. Sibling affectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
70
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 77 publications
7
70
1
1
Order By: Relevance
“…Early work by Dunn, Brown, and Maguire () and Dunn and Munn () demonstrated that warm, positive interactions with older siblings in early childhood were correlated with higher levels of cooperation and prosocial moral judgments in younger siblings at later ages. Subsequent cross‐sectional and longitudinal research, conducted with older children and adolescents using self‐ and parent‐reports, has also documented positive links between aspects of the sibling relationship and children's empathy and prosocial behavior (Harper, Padilla‐Walker, & Jensen, ; Lam et al., ; Pike, Coldwell, & Dunn, ; Tucker et al., ).…”
Section: The Development Of Empathic Concern In Early Childhoodmentioning
confidence: 99%
See 3 more Smart Citations
“…Early work by Dunn, Brown, and Maguire () and Dunn and Munn () demonstrated that warm, positive interactions with older siblings in early childhood were correlated with higher levels of cooperation and prosocial moral judgments in younger siblings at later ages. Subsequent cross‐sectional and longitudinal research, conducted with older children and adolescents using self‐ and parent‐reports, has also documented positive links between aspects of the sibling relationship and children's empathy and prosocial behavior (Harper, Padilla‐Walker, & Jensen, ; Lam et al., ; Pike, Coldwell, & Dunn, ; Tucker et al., ).…”
Section: The Development Of Empathic Concern In Early Childhoodmentioning
confidence: 99%
“…Although these findings suggest that siblings are implicated in children's empathy development, the conclusions that can be drawn from this existing work are constrained by methodological limitations. First, previous studies have primarily utilized cross‐sectional designs (Pike et al., ; Tucker et al., ), longitudinal models testing concurrent correlations (Lam et al., ), or have examined links between constructs over time without controlling for each siblings’ prior behavior (Dunn & Munn, ; Dunn et al., ; Harper et al., ). Unfortunately, such designs do not allow researchers to disentangle the unique contribution of older and younger siblings on the other's later development independent of other confounding variables (e.g., within‐sibling stability in empathy, shared exposure to parenting practices; Steele, Rasbash, & Jenkins, ).…”
Section: The Development Of Empathic Concern In Early Childhoodmentioning
confidence: 99%
See 2 more Smart Citations
“…Romano et al, 2005). For instance, children with siblings show more prosocial behaviour than firstborns or single children (e.g., Harper et al, 2014). In addition, different parenting styles have been linked to societal milieu and influence the development of prosocial behaviour (Liebenwein, 2008;Zahn-Waxler et al, 1979; see also Brooks-Gunn et al, 1993, for effects of neighborhood on children's development).…”
Section: Introductionmentioning
confidence: 99%